2007
DOI: 10.1158/0008-5472.can-07-1690
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antibody-Dependent Mechanisms of Tumor Cell Lysis by a Targeted Activator of Complement

Abstract: Complement inhibitors expressed on tumor cells provide a hindrance to the therapeutic efficacy of some monoclonal antibodies (mAb). We investigated a novel strategy to overwhelm complement inhibitor activity and amplify complement activation on tumor cells. The C3-binding domain of human complement receptor 2 (CR2; CD21) was linked to the complement-activating Fc region of human IgG1 (CR2-Fc), and the ability of the construct to target and amplify complement deposition on tumor cells was investigated. CR2 bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
(38 reference statements)
0
24
1
Order By: Relevance
“…They showed that human CR2-Fc is able to target to C3 activation products, enhances CDC in vitro and is effective in a mouse xenograft model. 5 The present study by Elvington et al provides data on therapeutic outcome with a murine CR2-Fc. Using 2 syngeneic mouse tumor models (metastatic lymphoma and melanoma), they demonstrate that coadministration of CR2-Fc with antitumor antibodies leads to better survival.…”
Section: Boosting Antibody Therapy With Complement ------------------mentioning
confidence: 82%
“…They showed that human CR2-Fc is able to target to C3 activation products, enhances CDC in vitro and is effective in a mouse xenograft model. 5 The present study by Elvington et al provides data on therapeutic outcome with a murine CR2-Fc. Using 2 syngeneic mouse tumor models (metastatic lymphoma and melanoma), they demonstrate that coadministration of CR2-Fc with antitumor antibodies leads to better survival.…”
Section: Boosting Antibody Therapy With Complement ------------------mentioning
confidence: 82%
“…Complement deposition, CDC and ADCC were significantly increased in the presence of a human CR2-Fc fusion protein. 117 In vivo biodistribution studies with the radioactively-labeled fusion protein confirmed its tumor specificity. In the final therapeutic study, mice bearing EL4 T cell lymphoma were treated with a tumor-specific mAb, the fusion protein or the combination.…”
Section: Inhibition Of Complement Regulatorsmentioning
confidence: 85%
“…CR2-Fc is able to both enhance C3 deposition with increased complement-mediated lysis and ADCC. 25) The strategy may be additive to all mAb effector mechanisms, including those that do not have ADCC and complement cytotoxicity as a recognized component of their primary mechanism of action. 25) Combination of these tools with anti-MUC1 mAb therapy may overcome OSCC and contribute to the development of strong effect and low side-effect therapy for OSCC.…”
Section: Discussionmentioning
confidence: 99%